Financial stress and Indigenous Australians - Robert Breunig; Syed Hasan; Boyd Hunter (Global Labor Organization (GLO), 2018)
We examine the high levels of financial stress among Indigenous populations in Australia. We estimate separate models for the determinants of financial stress for Indigenous and non-Indigenous households and show the importance of separately considering Indigenous disadvantage. We use these models to build equivalence scales for both groups. We find evidence consistent with financial stress being exacerbated by demand-sharing (“humbugging”). The evidence also suggests that financial stress is reduced by engagement in traditional hunting and gathering activities.
Keywords: I31; I32; J15; 330; financial stress; hardship; cashflow; equivalence scales; Indigenous poverty